2017
DOI: 10.22232/stj.2017.05.01.06
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Neem (Azadirachta indica A. Juss) Oil against Decay Fungi

Abstract: Abstract-The enormous use of metallic wood preservatives has caused destructive impact on environment as well as human health. Therefore realizing the urgency of switching to Environment friendly options such as natural oils are being tested for their antimicrobial properties. The present study aimed at investigating potential of Neem oil against the growth ofdecaying fungi. The ability of Neem oil to inhibit mycelia growth of Schizophyllum commune, Fusarium oxysporum, Fusarium proliferatum, Coniophora puteana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
1
1
0
1
Order By: Relevance
“…In the present experiment, the best results were obtained from Neem oil (T 5 ) followed by the Peppermint oil (T 6 ). Similar findings are also reported by Rawat et al, (2017) and Franca et al, (2018). The active ingredients of Neem oil are mostly of triterpinoids, e.g., nimbin, nimbidine, azadirachtin etc.…”
Section: Root Dry Weight (Gm)supporting
confidence: 92%
“…In the present experiment, the best results were obtained from Neem oil (T 5 ) followed by the Peppermint oil (T 6 ). Similar findings are also reported by Rawat et al, (2017) and Franca et al, (2018). The active ingredients of Neem oil are mostly of triterpinoids, e.g., nimbin, nimbidine, azadirachtin etc.…”
Section: Root Dry Weight (Gm)supporting
confidence: 92%
“…The best resistance was obtained for Scots pine sapwood treated with Artemisia monosperma , Citrus limon , Cupressus sempervirens , Pelargonium graveolens , Schinus molle and Thuja occidentalis oils. In turn, the effectiveness of neem oil, containing azadirachtin as a main antifungal compound, against S. commune , Fusarium oxysporum , Fusarium proliferatum , C. puteana and Alternaria alternate fungi was reported by Rawat et al [ 48 ]. Similar results were obtained by Hussain et al [ 30 ] who showed resistance of local Indian wood treated with neem oil against various moulds.…”
Section: Antifungal Substances Of Plant Originmentioning
confidence: 99%
“…Possivelmente, o uso do óleo de nim, nesta pesquisa, em maior concentração, proporcionou maior controle fúngico do que o alcançado por esses autores.Silva, Santos e Gomes (2014), analisando sementes de feijão-caupi tratadas com óleo de nim a 4%, obtiveram na cultivar maranhão controle 86% para Aspergillus sp.Neste trabalho, houve redução superior ao alcançado por esses autores com controle de 100% para Aspergillus sp. Provavelmente, a pulverização das sementes, ao invés de sementes submersas na diluição, proporcionou melhor adsorção do óleo de nim nas sementes, alcançando assim maior controle deste fitopatógeno.O óleo de nim em concentrações superiores a 2% foi capaz de inibir o crescimento micelial de Schizophyllum commune, Fusarium oxysporum, Fusarium proliferatum, Coniophora puteana e Alternaria alternata que causam podridão em madeira(RAWAT et al, 2017). Nesta pesquisa, o óleo de nim foi capaz de reduzir em 100% os fitopatógenos Aspergillus sp.…”
unclassified